Why is Pain Still Under‐Treated in the Emergency Department? Two New Hypotheses. (24th June 2015) - Carter, Drew; Sendziuk, Paul; Eliott, Jaklin A.; Braunack‐Mayer, Annette
Abstract: Across the world, pain is under‐treated in emergency departments (EDs). We canvass the literature testifying to this problem, the reasons why this problem is so important, and then some of the main hypotheses that have been advanced in explanation of the problem. We then argue for the plausibility of two new hypotheses: pain's under‐treatment in the ED is due partly to (1) an epistemic preference for signs over symptoms on the part of some practitioners, and (2) some ED practices that themselves worsen pain by increasing patients' anxiety and fear. Our argument includes the following logic. Some ED practitioners depart from formal guidance in basing their acute pain assessments on observable features rather than on patient reports of pain. This is potentially due to an epistemic preference for signs over symptoms which aims to circumvent intentional and/or unintentional misrepresentation on the part of patients. However, conducting pain assessments in line with this epistemic preference contributes to the under‐treatment of pain in at least three respects, which we detail. Moreover, it may do little to help the practitioner circumvent any intentional misrepresentation on the part of the patient, as we explain. Second, we examine at least four ED practices that may be contributing to the under‐treatment of pain by increasing patient anxiety and fear, which can worsen pain. These practices include failing to provide orienting information and partially objectifying patients so as to problem‐solve along lines pre‐established by modern medical science. We conclude by touching on some potential solutions for ED practice.